Peran Jampala dalam Meningkatkan Karakter Islami melalui Optimalisasi Media Sosial Followers Instagram @hwlamongan di Kwarda Hizbul Wathan Lamongan - Nashrul Mu'minin; Fathan Faris Saputro (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
This study explores the role of Jambore Prestasi Penghela (Jampala) Kwartir Daerah (Kwarda) Hizbul Wathan (HW) Lamongan in increasing engagement and the number of followers of the Instagram account @hwlamongan. Using a qualitative approach through in-depth interviews and observations, this study found that a planned social media management strategy and the use of attractive visual content during Jampala activities significantly increased user interaction and growth in the number of followers. The findings show that peak moments of the event and active participation of participants in social media content are key factors in the spike in engagement. Although challenges in maintaining engagement remain, these results emphasize the importance of activities such as Jampala as an effective digital promotional tool for scouting organizations.